2006
DOI: 10.1111/j.1742-4658.2006.05481.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and thermodynamic insights into the binding mode of five novel inhibitors of lumazine synthase from Mycobacterium tuberculosis

Abstract: Recently published genomic investigations of the human pathogen Mycobacterium tuberculosis have revealed that genes coding the proteins involved in riboflavin biosynthesis are essential for the growth of the organism. Because the enzymes involved in cofactor biosynthesis pathways are not present in humans, they appear to be promising candidates for the development of therapeutic drugs. The substituted purinetrione compounds have demonstrated high affinity and specificity to lumazine synthase, which catalyzes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 37 publications
3
56
0
Order By: Relevance
“…The energy minimization procedure turned the indole ring of Trp-27 to a parallel conformation with respect to the plane of the aromatic groups of all inhibitors, whereas the indole group in the empty structure assumed different conformations in different subunits. This conformational change of the side chain of Trp-27 is in good agreement with the conformations of the aromatic groups of tryptophan or phenylalanine found in the structures of different LSs inhibitor complexes (9,10,12,18,49,52,53). The main-chain contacts, found conserved in all orthologous complexes, remained unchanged in the binding models of all inhibitors.…”
Section: Cals/ts13 Cals/ts44 Cals/gj43 Cals/jc33supporting
confidence: 69%
See 1 more Smart Citation
“…The energy minimization procedure turned the indole ring of Trp-27 to a parallel conformation with respect to the plane of the aromatic groups of all inhibitors, whereas the indole group in the empty structure assumed different conformations in different subunits. This conformational change of the side chain of Trp-27 is in good agreement with the conformations of the aromatic groups of tryptophan or phenylalanine found in the structures of different LSs inhibitor complexes (9,10,12,18,49,52,53). The main-chain contacts, found conserved in all orthologous complexes, remained unchanged in the binding models of all inhibitors.…”
Section: Cals/ts13 Cals/ts44 Cals/gj43 Cals/jc33supporting
confidence: 69%
“…(20,21,48). It has been shown that the purinetrione ring system with an attached C5-phosphate side chain resulted in a less potent inhibitor of B. subtilis LS (20); however, it revealed a high inhibition potential for the pentameric enzyme from M. tuberculosis (12,20,49). The present investigation of binding processes has shown that the values of the association constants of those inhibitors to CALS are in a similar range compared with those for M. tuberculosis LS.…”
Section: Cals/ts13 Cals/ts44 Cals/gj43 Cals/jc33mentioning
confidence: 57%
“…Almost 100,000 compounds have been tested for inhibition of RF biosynthetic enzymes (279,314,316,491,553). Some compounds were very efficient inhibitors in vitro, and a few of them displayed antibiotic activity against M. tuberculosis.…”
Section: The Riboflavin Biosynthesis Pathway As a Target For Antimicrmentioning
confidence: 99%
“…M. tuberculosis is absolutely dependent on the endogenous synthesis of riboflavin because it is unable to take up the vitamin from the environment. On the other hand the enzymes involved in this pathway are not present in the human or any other animals which makes them promising candidates for the inhibition of bacterial growth (Morgunova et al, 2006). Lumazine synthase (LS) and riboflavin synthase are two enzymes in the riboflavin biosynthesis pathway (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Figure.1 A schematic diagram of terminal reactions that are catalyzed by lumazine synthase and riboflavin synthase in the pathway of riboflavin biosynthesis. (A) 5-amino-6-ribitylamino-2,4(1H,3H)-pyrimidinedione; (B) 3,4-dihydroxy-2-butanone 4-phosphate; (C) 6,7-dimethyl-8-ribityllumazine; and (D) riboflavin So far various pyrimidine or purine ring containing compounds were reported as potent inhibitors of LS (Persson et al, 1999;Gerhardt et al, 2002;Morgunova et al, 2005;Morgunova et al, 2006;Zhang, Y. et al, 2008;Zhang, X. et al, 2008). These compounds were almost identical to substrate of LS (designated as A in figure1) and inhibit the activity of the enzyme in competitive mechanism.…”
Section: Introductionmentioning
confidence: 99%